Blood vessel modelling and simulation of the blood flow - Shi, Minjie (2014)
The blood vessels is an important part of the human body. Every year, thousands of people die because of the vessel related diseases. The modelling and simulation of blood vessels can help people understand these diseases better. The aim of this project is to find the processes involved in computational fluid dynamics using OpenFOAM and create appropriate vessel models to do the simulation. Different simulation results are presented and compared. The factors that could affected the simulation results are explored and it has been found that the quality of the mesh plays the key rule for the simulation result. In addition, a graphic user interface is created by applying software engineering principles in order to make the simulation of the blood flow in two branches easier. The future work for this area field is listed in the last chapter.